Interaction Between Arbuscular Mycorrhizal and Antagonistic Rhizosphere Fungi in Peat Soil Enhancing Growth of Coffea liberica Seedlings - Elis Kartika; Made Deviani Duaja; Gusniwati Gusniwati; Zulkarnain Zulkarnain (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
This study aimed at determining the effect of Arbuscular Mycorrhizal Fungi (AMF) and Antagonistic Rhizosphere Fungi (ARF) on growth of Coffea liberica seedlings in peat soils. Eight AMF isolates (without AMF, Glomus sp.-1a, Glomus sp.-3c, Acaulospora sp.-1b, Acaulospora sp.- 2d, Glomus sp.-1a + Glomus sp.-3c, Acaulospora sp.-1b + Acaulospora sp.-2d, and mixtures of Glomus sp.-1a + Glomus sp.-3c + Acaulospora sp.-1b + Acaulospora sp.-2d) were combined with five ARF types (without ARF, Trichoderma sp., Aspergillus sp., Gliocladium sp., and Penicillium sp.). Data were collected on the following variables: seedling height, leaf number, stem diameter, shoot and root dry weight, N and P uptake, and root infection by AMF. Results indicated that Trichoderma sp., in combination with various types of AMF, was the best ARF in promoting C. liberica seedling growth and increasing N and P uptake. On the other hand, the mixture of Glomus sp.-1a + Glomus sp.-3c combined with various types of ARF was the best AMF in promoting seedling growth and increasing N and P uptake. It can be concluded that Trichoderma sp. and the mixture of Glomus sp-1a and Glomus sp-3c were best combination to be applied to promote the C. liberica seedlings grown in peat soil.